2019
DOI: 10.3390/data4010037
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial and Temporal Distribution of Process Gases within the Biowaste Compost

Abstract: Composting is generally accepted as the sustainable recycling of biowaste into a useful and beneficial product for soil. However, composting processes can produce gases that are considered air pollutants. In this dataset, we summarized the spatial and temporal distribution of process gases (including rarely reported carbon monoxide, CO) generated inside full-scale composting piles. In total 1375 cross-sections were made and presented in 230 figures. The research aimed to investigate the phenomenon of gas evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 14 publications
6
42
0
Order By: Relevance
“…In a wintertime experiment of composting with passive aeration [45], cooling began at the ends of the pile, which was explained by the increased surface area of the material and therefore increased heat loss. In this study, a similar pattern of temperature drop was observed only in piles A1 (36th day of the process, [43] ( Figure A4)), A2 (15th and 23rd day, [43] (Figures A8 and A9)), and A3 (15th and 52nd day, [43] (Figures A17 and A22)), where it took place on just one end. Also, in some cases, areas that had previously cooled down reached a higher temperature at later stages of composting (e.g., the end of the left side of pile A6 at day 29 [43] ( Figure A43)).…”
Section: Spatial and Temporal Distribution Of Temperature Within The supporting
confidence: 79%
See 3 more Smart Citations
“…In a wintertime experiment of composting with passive aeration [45], cooling began at the ends of the pile, which was explained by the increased surface area of the material and therefore increased heat loss. In this study, a similar pattern of temperature drop was observed only in piles A1 (36th day of the process, [43] ( Figure A4)), A2 (15th and 23rd day, [43] (Figures A8 and A9)), and A3 (15th and 52nd day, [43] (Figures A17 and A22)), where it took place on just one end. Also, in some cases, areas that had previously cooled down reached a higher temperature at later stages of composting (e.g., the end of the left side of pile A6 at day 29 [43] ( Figure A43)).…”
Section: Spatial and Temporal Distribution Of Temperature Within The supporting
confidence: 79%
“…In this study, a similar pattern of temperature drop was observed only in piles A1 (36th day of the process, [43] ( Figure A4)), A2 (15th and 23rd day, [43] (Figures A8 and A9)), and A3 (15th and 52nd day, [43] (Figures A17 and A22)), where it took place on just one end. Also, in some cases, areas that had previously cooled down reached a higher temperature at later stages of composting (e.g., the end of the left side of pile A6 at day 29 [43] ( Figure A43)). It was also observed that low temperatures (prevailing in the piles in autumn and winter) were caused by an unfavorable surface-to-volume ratio, which resulted in faster heat loss (Table 3) [46].…”
Section: Spatial and Temporal Distribution Of Temperature Within The supporting
confidence: 79%
See 2 more Smart Citations
“…The software will optimize the carbonized refuse-derived fuel (CRDF) production process before its valorization in the torrefaction process. In addition, the appropriate selection of the MSW mixture will help determine the cost-effectiveness of MSW mechanical pre-treatment and torrefaction of individual, site-specific wastes, waste streams, and their mixtures, such as municipal sludge [9] or compost [10].…”
Section: User Notesmentioning
confidence: 99%